The energy efficiency gap and barriers to investments - Leon Bremer; Sacha J. den Nijs; Henri L.F. de Groot (Tinbergen Institute, 2023)
This study investigates the energy efficiency (EE) gap, referring to private agents who are not making seemingly profitable investments to reduce energy use. We deploy a questionnaire among firms in the Netherlands in which we ask them about investment behavior and barriers to investing in EE. A set of 16 barriers is constructed based on the literature. We find that most firms (70%) have made EE investments in the past five years, and that the median firm has saved 10% of its energy use. The remaining profitable EE investment opportunities still leave room for another 15% of energy savings at the median firm. We find that uncertainty about future policies ranks as the leading barrier to EE investments, followed by lock-ins in current equipment, and energy price uncertainty. Especially energy-intensive firms indicate the importance of policy uncertainty. Past policies have not been successful in addressing these barriers. Additionally, we find that a firm's network can be an important channel for obtaining EE investment knowledge. Classification-JEL: C83, D22, O33, Q40.
Keywords: C83; D22; O33; Q40; 330; energy efficiency gap; barriers; investment behavior; technology adoption; policy uncertainty